CHARACTERISTICS OF THYROID DISEASE IN WOMAN WITH RHEUMATOID ARTHRITIS (World Bulletin of Social Sciences, 2024)
The chronic progressive course of RA poses the task of doctors to diagnose it as early as possible. However, recognition of RA at an early stage presents significant difficulties. To date, no strictly RA-specific laboratory test has been found. Only a combination of many clinical and laboratory signs can help in the diagnosis of this disease. Therefore, the search for methods to differentiate rheumatoid arthritis among a variety of inflammatory and degenerative diseases of the musculoskeletal system continues. According to modern concepts, connective tissue damage in RA is a consequence of developing immunopathological disorders. The autoimmune nature of RA is evidenced by the detection of rheumatoid factor (RF), circulating immune complexes (CIC), lymphocytes sensitized to connective tissue components, as well as a wide range of autoantibodies (AT)